2020
DOI: 10.1111/eci.13246
|View full text |Cite
|
Sign up to set email alerts
|

MR‐ proADM to detect specific types of organ failure in infection

Abstract: Background: Following the SEPSIS-3 consensus, detection of organ failure as assessed by the SOFA (Sequential Organ Failure Assessment) score, is mandatory to detect sepsis. Calculating SOFA outside of the Intensive Care Unit (ICU) is challenging. The alternative in this scenario, the quick SOFA, is very specific but less sensible. Biomarkers could help to detect the presence of organ failure secondary to infection either in ICU and non-ICU settings. Materials and methods: We evaluated the ability of four bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In fact, levels of MR-proADM can potentially reflect the severity of organ dysfunction, even in the first stages of the disease, in the progression of systemic inflammatory response, in the movement from sepsis to septic shock, and in the mortality risk of septic patients [ 11 , 12 ]. A prospective observational study conducted with 213 septic patients showed that MR-proADM was able to predict system dysfunction (respiratory, coagulation, renal, neurological, and cardiovascular) and was well-correlated with Sequential Organ Failure Assessment (SOFA) score components [ 13 ]. The same results were obtained by Onal et al [ 11 ], who concluded that MR-proADM could be a good alternative to SOFA score.…”
Section: Role Of Mr-proadm In Icu and In Edmentioning
confidence: 99%
“…In fact, levels of MR-proADM can potentially reflect the severity of organ dysfunction, even in the first stages of the disease, in the progression of systemic inflammatory response, in the movement from sepsis to septic shock, and in the mortality risk of septic patients [ 11 , 12 ]. A prospective observational study conducted with 213 septic patients showed that MR-proADM was able to predict system dysfunction (respiratory, coagulation, renal, neurological, and cardiovascular) and was well-correlated with Sequential Organ Failure Assessment (SOFA) score components [ 13 ]. The same results were obtained by Onal et al [ 11 ], who concluded that MR-proADM could be a good alternative to SOFA score.…”
Section: Role Of Mr-proadm In Icu and In Edmentioning
confidence: 99%
“…Finally, Bermejo et al analyzed the ability of MR-ProADM and other markers to detect the different possible organ failures in patients with infection. In his research, the AUC-ROC of MR-ProADM for the diagnosis of organ failure was 0.79 (0.72–0.86), considered a very good predictive capacity, above that obtained with other biomarkers studied in the same work such as PCT: 0.62 (0.54–0.70), lactate: 0.69 (0.61–0.78), or CRP: 0.54 (0.45–0.63) [ 66 ]. Biomarkers could add valuable information to clinical judgment to detect the presence of organ failure early on during infection.…”
Section: The Best Biomarkers In Intensive and Perioperative Carementioning
confidence: 86%
“…It has biological properties, including vasodilating, inotropic, diuretic, natriuretic, and bronchodilating. In one study, mid-regional pro adrenomedullin (MR-proADM) was an independent predictor of five different organ failures (respiratory, coagulation, cardiovascular, neurological, and renal), compared to lactate which predicted three (coagulation, cardiovascular and neurological), PCT two (cardiovascular and renal) and CRP (none) [50]. MR-proADM most accurately identified patients with a high likelihood of further disease progression compared to other biomarkers and clinical scores [51].…”
Section: Hormones and Peptide Precursorsmentioning
confidence: 99%